STUDY OF STUDENT’S INTENTION TO USE ELECTRONIC MONEY BASED ON TAM - Rahim, Raihan Maldini (Jurnal Ilmiah Mahasiswa FEB, 2019)
Electronic money is a technology that can truly change Indonesian social life. However, the successful implementation of electronic money depends on how much the level of public self-efficacy in its use and the risks that consumers will face when adopting it. The purpose of this study is to examine the factors that influence the behavioral intention of consumers to use electronic money. This study uses the theory of Technology Acceptance Model (TAM) with additional perceived of risk and self-efficacy as external variables. This research is a quantitative research and questionnaires as the data collection tool. Respondents were 347 active undergraduate students from the Accounting Department in the Faculty of Economics and Business, Universitas Brawijaya. The research data and hypothesis are analyzed using structural equation modeling (SEM) based on Partial Least Squares (PLS). The results of this study indicate that behavioral intention to use electronic money is significantly and positively influenced by perceived usefulness and perceived ease of use. Furthermore, perceived usefulness and perceived ease of use are negatively influenced by perceived of risk. In contrast, perceived usefulness and perceived ease of use are positively influenced by self-efficacy. Keywords: E-money, Perceived Risk, Self-efficacy, TAM